2003
DOI: 10.1073/pnas.2235808100
|View full text |Cite
|
Sign up to set email alerts
|

Biomagnification of cyanobacterial neurotoxins and neurodegenerative disease among the Chamorro people of Guam

Abstract: We here report biomagnification (the increasing accumulation of bioactive, often deleterious molecules through higher trophic levels of a food chain) of the neurotoxic nonprotein amino acid ␤-methylamino-L-alanine (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
389
1
12

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 546 publications
(411 citation statements)
references
References 18 publications
9
389
1
12
Order By: Relevance
“…Cyanobacteria also can negatively affect domestic and wild animals as well as human health since they have the potential to produce toxins (see overview Merel et al 2013), and numerous animal and human intoxications by cyanobacterial toxins have been reported (e.g. Kuiper-Goodman et al 1999;Cox et al 2003;Griffiths and Saker 2003;Hilborn et al 2007). Hence, cyanobacterial dominance in water systems can have serious economical and societal consequences as it impedes important ecosystem services of inland waters including recreational use, aquaculture, water usage for irrigation and drinking water usage (Paerl and Huisman 2009;Ibelings et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Cyanobacteria also can negatively affect domestic and wild animals as well as human health since they have the potential to produce toxins (see overview Merel et al 2013), and numerous animal and human intoxications by cyanobacterial toxins have been reported (e.g. Kuiper-Goodman et al 1999;Cox et al 2003;Griffiths and Saker 2003;Hilborn et al 2007). Hence, cyanobacterial dominance in water systems can have serious economical and societal consequences as it impedes important ecosystem services of inland waters including recreational use, aquaculture, water usage for irrigation and drinking water usage (Paerl and Huisman 2009;Ibelings et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, several bloom-forming cyanobacteria produce toxins, causing serious and sometimes fatal liver, digestive and neurological diseases in birds and mammals, including humans (Carmichael, 2001;Cox et al, 2003;Codd et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that BMAA is produced by cyanobacteria of the genus Nostoc, which are root symbionts of cycads (1). BMAA is then biomagnified in both the cycad seeds and the flying foxes that forage on them.…”
mentioning
confidence: 99%
“…Consumption of flying foxes by the Chamorro people has been implicated as a delivery mechanism of relatively high doses of BMAA in the Chamorro diet (6,7). Support for this hypothesis has come from the findings of high levels of BMAA in Guam flying foxes (8) and the discovery of BMAA within brain tissues of Chamorro patients who have died of ALS͞PDC in Guam (1).…”
mentioning
confidence: 99%